2013
DOI: 10.1063/1.4829363
|View full text |Cite
|
Sign up to set email alerts
|

Optical diode based on exciton-polaritons

Abstract: We propose theoretically an optical diode based on exciton-polaritons in semiconductor microcavities. A flow of polaritons in the bistable regime is used to send signals through an asymmetric fixed potential that favours the tunneling of particles in one direction. Through dynamic modelling of the coherent polariton field, we demonstrate the characteristics of an ideal diode, namely that the forward signal is fully transmitted while the transmission in the reverse direction tends to zero, without any additiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…It has been shown that exciton-polariton systems give rise to bistability under resonant pumping schemes [5][6][7] with applications in photonic logic gates [8][9][10] , switches and memory elements [11][12][13] , control of polariton superfluids 14 , and optical diodes 15 . Under resonant excitation a number of works focused on the parametric instability between polaritons [16][17][18][19][20] , where polaritons in one particular energy-momentum state scatter in pairs to "signal" and "idler" states conserving energy and momentum.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that exciton-polariton systems give rise to bistability under resonant pumping schemes [5][6][7] with applications in photonic logic gates [8][9][10] , switches and memory elements [11][12][13] , control of polariton superfluids 14 , and optical diodes 15 . Under resonant excitation a number of works focused on the parametric instability between polaritons [16][17][18][19][20] , where polaritons in one particular energy-momentum state scatter in pairs to "signal" and "idler" states conserving energy and momentum.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, room temperature operation of an all-optical binary switch was indeed demonstrated using self-assembled perovskite microwires [142] . Other required optical components such as memory devices [143,144] , diodes [145,146] , routers [147][148][149] , and optical amplifiers [150] are required for room temperature optical computing. A universal logic gate set and a method of cascading them are also required [151] .…”
Section: Optical Computingmentioning
confidence: 99%
“…yyzhang@bit.edu.cn [19]. These developments are the foundation of the accurate design of the microcavity devices, such as optical diodes [20] and quantum circuits [21][22][23]. Generally speaking, it is easier to design the photonic potentials than to design the excitonic ones.…”
Section: Introductionmentioning
confidence: 99%